Effect of thermal interaction between bulk GaN substrates and corral sapphire on blue light emission InGaN/GaN multi-quantum wells by MOCVD - Sivanathan, P.C.; Shuhaimi, Ahmad; Hamza, Hebal; Kowsz, Stacy J.; Abdul Khudus, Muhammad Imran Mustafa; Li, Hong Jian; Allif, Kamarul (Elsevier, 2018)
The InGaN/GaN multi-quantum wells, growth on bulk GaN substrate were studied for blue light emission. Growth temperature plays a key role determining the peak wavelength of a quantum well. The study was carried out by growing quantum wells, MQWs on the whole sapphire at 716 °C and observed peak wavelength at 463 nm. While the bulk GaN substrate with sapphire corral grown at 703 °C and observed a blueshift at 433 nm peak wavelength. These results contradict that of typical observation of wavelength emission inversely proportional to the growth temperature. On the other hand, the growth of GaN-sapphire and GaN-silicon at similar conditions emits 435 nm and 450 nm respectively. The heat interaction of bulk GaN substrates surrounded by the sapphire corral exhibits different growth conditions in multi-quantum wells when compared to that of a whole sapphire substrate (absence of bulk GaN). The predicated surface temperature of bulk GaN substrate is 10 °C–15 °C of more than the corral sapphire. This observation may link to the difference in the thermal distribution of the growth surface corresponding to the different thermal conductivity ratio. The photoluminescence and computational techniques were used to understand in-depth of the heat interaction.